2015
DOI: 10.1186/s12913-014-0670-6
|View full text |Cite
|
Sign up to set email alerts
|

Information-gathering for self-medication via Eastern Indonesian community pharmacies: a cross-sectional study

Abstract: BackgroundGathering sufficient information when handling self-medication requests in community pharmacies is an important factor in assisting patients to obtain appropriate health outcomes. Common types of information usually gathered include patient identity, signs and symptoms, action taken, medical history, and current medications being used. The aims of the study were (1) to describe the types and amount of information gathered by Eastern Indonesian community pharmacy staff when handling self-medication re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 20 publications
1
38
0
3
Order By: Relevance
“…Critically, the pharmacists' skills were not significantly different from those of other staff members. (Brata, Marjadi, Schneider, Murray, & Clifford, ; Puspitasari, Faturrohmah, & Hermansyah, ). Although poor communication cannot be solely attributed to deficiencies in education, these studies nonetheless demonstrated the need for inclusion of increased social and clinical content in the pharmacy curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Critically, the pharmacists' skills were not significantly different from those of other staff members. (Brata, Marjadi, Schneider, Murray, & Clifford, ; Puspitasari, Faturrohmah, & Hermansyah, ). Although poor communication cannot be solely attributed to deficiencies in education, these studies nonetheless demonstrated the need for inclusion of increased social and clinical content in the pharmacy curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Underpinning these factors, pharmacist variability during information gathering about patients' smoking-status may result from the lack of a standardised protocol covering the kind of information that should be gathered during pharmacist consultations. [43] In Australia, pharmacists are required to ask smoking information (status and number of cigarettes) from patients only when providing disease state management services, which is financially incentivised for only four health conditionsdiabetes, respiratory, cardiovascular disease and mental health conditions. [44] This is the first study to assess pharmacist smoking cessation practices in patients who smoke and present with an oral health condition/enquiry.…”
Section: Discussionmentioning
confidence: 99%
“…Almost 50% of pharmacist in Indonesia is registered as pharmacist in charge in community pharmacy [12]. Pharmacist role in community is very important because they can meet and consult the patient who come their pharmacy [13,14]. To conduct this, pharmacy student need to have communication skill during their study.…”
Section: Discussionmentioning
confidence: 99%